2023
DOI: 10.1162/jocn_a_02012
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Entrainment Reveals Statistical Learning across Levels of Abstraction

Abstract: We encounter the same people, places, and objects in predictable sequences and configurations. Humans efficiently learn these regularities via statistical learning. Importantly, statistical learning creates knowledge not only of specific regularities but also of regularities that apply more generally across related experiences (i.e., across members of a category). Prior evidence for different levels of learning comes from post-exposure behavioral tests, leaving open the question of whether more abstract regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…I next asked whether a basic Hebbian learning model can explain periodic neural activity (e.g., Batterink, 2020; Batterink & Paller, 2017; Benjamin, Fló, Palu et al., 2023; Buiatti et al., 2009; Choi et al., 2020; Fló et al., 2022; Henin et al., 2021; Kabdebon et al., 2015; Moreau et al., 2022; Moser et al., 2021; Sherman et al., 2023), at least for the forgetting rates for which the network preferred words to part‐words. In a first analysis, I recorded the total network activation after each syllable in a word had been presented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…I next asked whether a basic Hebbian learning model can explain periodic neural activity (e.g., Batterink, 2020; Batterink & Paller, 2017; Benjamin, Fló, Palu et al., 2023; Buiatti et al., 2009; Choi et al., 2020; Fló et al., 2022; Henin et al., 2021; Kabdebon et al., 2015; Moreau et al., 2022; Moser et al., 2021; Sherman et al., 2023), at least for the forgetting rates for which the network preferred words to part‐words. In a first analysis, I recorded the total network activation after each syllable in a word had been presented.…”
Section: Resultsmentioning
confidence: 99%
“…Strong evidence in favor of this possibility comes from electrophysiology, where rhythmic activity has been observed in response to statistically structured sequences. In the time domain, different authors have observed amplitude peaks around the boundaries of statistically defined words (e.g., Abla et al., 2008; Cunillera et al., 2006; Kudo et al., 2011; Sanders et al., 2002; Teinonen et al., 2009); in the frequency domain, a frequency response with a period of the word duration emerges as participants learn the statistical structure of the speech stream (e.g., Batterink, 2020; Batterink & Paller, 2017; Benjamin, Fló, Palu et al., 2023; Buiatti et al., 2009; Choi et al., 2020; Fló et al., 2022; Henin et al., 2021; Kabdebon et al., 2015; Moreau et al., 2022; Moser et al., 2021; Sherman et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While category representations can be found elsewhere in the brain (Mansouri et al, 2020), it is apparent that, across both tasks (Blank & Bayer, 2022;Mack et al, 2013) and methodologies (Sherman et al, 2023), specific and general representations of experience may form in parallel.…”
Section: Discussionmentioning
confidence: 99%